Does Commons Grabbing Lead to Resilience Grabbing? The Anti-Politics Machine of Neo-Liberal Development and Local Responses - Haller, Tobias; Käser, Fabian; Ngutu, Mariah (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue contributes to the debate on land grabbing as commons grabbing with a special focus on how the development of state institutions (formal laws and regulations for agrarian development and compensations) and voluntary corporate social responsibility (CRS) initiatives have enabled the grabbing process. It also looks at how these institutions and CSR programs are used as development strategies of states and companies to legitimate their investments. This Special Issue includes case studies from Kenya, Morocco, Tanzania, Cambodia, Bolivia and Ecuador analysing how these strategies are embedded into neo-liberal ideologies of economic development. We propose looking at James Ferguson's notion of the Anti-Politics Machine (1990) that served to uncover the hidden political basis of state-driven development strategies. We think it is of interest to test the approach for analysing development discourses and CSR-policies in agrarian investments. We argue based on a New Institutional Political Ecology (NIPE) approach that these legitimize the institutional change from common to state and private property of land and land related common pool resources which is the basis of commons grabbing that also grabbed the capacity for resilience of local people.